Socioeconomic and Cultural Importance of The Yellow-Fronted Canary (Serinus Mozambicus) in Northern Benin - Adoté Hervé Gildas. Akueson; Marcel Gbaguidi Alia; Sissou Zakari; Arcadius Yves. Justin. Akossou (European Scientific Journal, ESJ, 2021)
The species yellow-fronted canary undergoes a real traffic due to its song and medico-magical properties in order to supply local commercial networks. This study aims to assess the socioeconomic and cultural importance of this bird in order to identify the cohorts of actors involved along this activity chain. In this context a survey was carried out among 400 breeders in four agroecological zones of Benin (ZAE II; ZAE III, ZAE IV and ZAE V). The questionnaire also focused on general characteristics of the respondents on aspects related to general knowledge of the bird, its social importance, purchase and sale price, cultural importance and breeders’ perceptions. Canary traders, mostly with primary education level (63.25%) and Muslim (97.5%), were on average 44 years old and an average experience of 27 years. They exercised this activity in part-time (96.5%). The knowledge about canary is shared is different depending on the ethnic group. The activity was profitable for all of them (100%) with 128,624 FCFA (233.18 USD) net profit per month. The trader's education level, whether or not he belonged to ZAE II, the number of birds he had in his possession, the daily amount he invested in their food, their selling price, the number of years he made the activity, his experience in the business were the factors that determine the net profit of the canary’s trader. However, canaries' breeding in north-Benin is based on a complex system with actors who develop many myths around medico-magical practices. This study was necessary to better assess the pressure on the species in order to anticipate its conservation.